The effects of Zara to the SMEs of an emerging market - PELTEKOĞLU, ZEYNEP FİLİZ (Routledge, 2011)
Globalization can be described as a systematic decline in the boundaries of the cross-national flow of products, values, ideas, labors and capitals. In other words, globalization disregards any physical boundaries and wipes out the classical meaning of domestic market. Therefore it creates a true challenge for every local enterprise but especially for SMEs (Small and Medium Enterprises) of the emerging countries since competition is increasing and every local industry is losing its exclusively national character by globalization. While the definition of SMEs can easily be a topic of an academic paper, SMEs are commonly regarded as small business systems with some unique characteristics. Some of these unique characteristics are positive business attributes such as flexibility, independency, informality, innovative behaviour, operation possibilities on slim margins, high motivation of employees, short decision-making chains, and negative attributes such as limited financial, managerial, human and informational resources. Besides these attributes, SMEs are mostly defined as local businesses, significantly having highly personalized management styles, employing less than one hundred employees. As SMEs are more vulnerable, especially due to the lack of financial resources, most of the SMEs can’t meet the needs of the global competition and get vitally effected by the growing pace of globalization. It is known that SMEs are significantly important for a country’s financial environment, therefore the relatively high rate of SMEs failure can easily damage the economy of any country. This fact is especially true in emerging countries where economies are fragile and any kind of failure is harmful. Yet the interest of global companies towards creating global brands has a negative impact on the SMEs of the emerging countries. As the relative prices of SMEs products fall due to the increased global competition, these firms find themselves in financially difficult positions especially in terms of cash flow circulation. Under the pressure of globalization, enterprises encounter major challenges that can be summarized as retaining short-term competitive advantages, reacting to globalization challenges in real-time and solving issues concerning long-term competitiveness. One good example of globalization’s negative effects on SMEs is as seen in the clothing industry by the global brand Zara. The global fashion brand Zara, the subsidiary of the Spanish Inditex Group, is credited as the leading company of fast-fashion. The brand, that was ranked 73rd on the list of the world’s 100 top brands 2006 by Interbrand, has transformed itself from a local brand to a global brand in less than 30 years. The success of Zara basically comes from the change it has made to fashion industry; from changing fashion from an elite accessory of the super-rich to a mass-market product. Additionally Zara handles fashion products as non-du-rable and disposable items with a maximum three to four week sell-by period and this mentality is called fast-fashion. It’s been observed that customers react to the fast-fashion approach differently and estimated that customers visit Zara stores 17 times a year on average. As the result of these frequent visits, Zara handles a great velocity of sales, in 2008 Zara has announced 10,407.435 million € turnover with 1,253 million € profit. Since Zara’s products are not associated with any coun-try-specific image, they are labeled as global products representing global fashion trends. With this global appeal, Zara became very successful in every country within a short period of time, inevitably effected every local market, and Turkey wasn’t an exception. Turkish clothing industry is relatively an important player of the global arena as it is the world’s sixth biggest ready-wear manufacturer and The European Union’s second largest supplier after China. The industry is typically characterized by small, low-capital, family-run businesses, many of which has simple operations generally with no original designs. Since most of the companies are family owned and managed by the entrepreneur, the industry is left without well-trained, professional management. Short term gains are becoming more important than long term goals, therefore the industry is falling behind from brand investments, research and development. Another major issue of the SMEs are the high energy costs and unpredictable power cuts. Additional to energy problems there is the issue of high rates of taxes and financing. These high rates causes another disadvantage to the SMEs as these costs are cutting down most of their profit. Labour costs which represent 12 to 20% of production costs, is another problematic issue. Although labour costs remain low compared to Europe, it is still much higher than in Asia. Yet despite the negative developments, the industry has been able to compete successfully in the global arena. But since globalization has broadened the challenges and fashion brands such as Zara has entered the domestic market, the cost-based competition with an increased time pressure demand will be shaping the Turkish industry in near future. After the brief literature review, this paper provides a close-look at Zara’s effects on SMEs of Turkish clothing industry by utilizing a survey of 50 SMEs that are active in one of the busiest retail districts of the industry. As for the outcome of the survey, it is found that all SMEs are strongly effected by the entrance of Zara in terms of competition, increase in the number of items, pricing and decrease in the quantity of items. As for the result of Two Step Cluster Analysis two main cluster group of SMEs are defined. The first cluster, which is formed by SMEs targeting women, working in the market for at least 10 years with more than 25 employees is definitely effected by the entrance of Zara. Where second cluster, which is formed by SMEs targeting other than women, working in the market for less than 10 years with less than 25 employees is less effected by Zara. © 2011 KAMS. All rights reserved.
Keywords: Fast-fashion; Globalization; SMEs; Turkish clothing industry; Zara